2009
DOI: 10.1159/000270154
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cranial Osteomyelitis in an Otherwise Healthy Ten-Year-Old Male

Abstract: Frontal bone osteomyelitis is a relatively rare entity, particularly in the otherwise healthy pediatric population. Most cases trace their origins to either previous frontal sinusitis or trauma. In children, three origins for cranial osteomyelitis appear to dominate: Pott’s puffy tumor, skull base osteomyelitis secondary to ear infection, or post-surgical complications. However, on extremely rare occasions, risk factors or etiology may not be ascertained. We present a case of spontaneous frontal bone osteomyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Most of the articles were either case series or case reports. The characteristics of the included studies are summarized in Table …”
Section: Resultsmentioning
confidence: 99%
“…Most of the articles were either case series or case reports. The characteristics of the included studies are summarized in Table …”
Section: Resultsmentioning
confidence: 99%
“…36 Common causes in children are complicated frontal sinusitis, skull base osteomyelitis secondary to ear infection and postsurgical infection. 37 CT demonstrates a lytic permeative pattern of osseous involvement in the acute phase. In the chronic phase, a mixed lytic and sclerotic pattern may be observed.…”
Section: Skull Base Osteomyelitismentioning
confidence: 97%
“…In children, three origins for cranial osteomyelitis appear to dominate: Pott's puffy tumor, skull base osteomyelitis secondary to ear infection, or postsurgical complications. However, on extremely rare occasions, risk factors or etiology may not be ascertained (Arnold et al, 2009). Arnold et al (Arnold et al, 2009) reported a case of spontaneous cranial osteomyelitis in an otherwise healthy child.…”
Section: Spontaneous Cranial Osteomyelitis In An Otherwise Healthy Childmentioning
confidence: 99%
“…However, on extremely rare occasions, risk factors or etiology may not be ascertained (Arnold et al, 2009). Arnold et al (Arnold et al, 2009) reported a case of spontaneous cranial osteomyelitis in an otherwise healthy child.…”
Section: Spontaneous Cranial Osteomyelitis In An Otherwise Healthy Childmentioning
confidence: 99%